Are Posttraumatic Stress Symptoms and Avoidant Coping Inhibitory Factors? The Association Between Posttraumatic Growth and Quality of Life Among Low-Grade Gliomas Patients in China - Li, Junyi; Sun, Lijun; Wang, Xiaoyu; Sun, Cuicui; Heng, Shupeng; Hu, Xiangen; Chen, Wei; Liu, Fujun (Frontiers in Psychology, 2019)
Background Diagnosing with low-grade gliomas (LGGs) can be a very shocking and stressful experience, a traumatic event potentially leading to the development of posttraumatic stress symptoms (PTSS) and posttraumatic growth (PTG). Understanding how patients cognitively and behaviorally response to their diagnosing is also important to postoperative treatment. Thus, the current study explored the association between PTG and quality of life (QoL) of Chinese patients with LGGs. The moderation effects of coping strategies and PTSS on the relationship between PTG and QoL have been examined as well. Method PTSS, PTG, coping strategies, and QoL were measured by using self-report surveys. Three hundred and thirty patients completed surveys approximately one month after surgery. We used three multiple regression models and added interaction terms in these models to test the moderation effects of PTSS and coping strategies on the relationship between PTG and QoL. Results The results of hierarchical multiple regression suggested that PTG significantly predicted QoL, both PTSS and coping strategies moderated the association between PTG and QoL. Specifically, the association between PTG and QoL for patients who have non-significant PTSS is stronger than those who have significant PTSS. Furthermore, as the score of Avoidant Coping increases, the association between PTG and QoL becomes weaker. Conclusions PTG may help to improve the QoL of LGGs patients, but PTSS and Avoidant Coping impeded the positive effect of PTG on QoL.